Secondary traumatic stress and posttraumatic growth in newly graduated nurses: the mediating role of compassion satisfaction - Li Zeng; Xiangeng Zhang; Guiling Liu; Dong Liu; Lan Li; Man Jin; Xin Li; Jialin Wang (BMC, 2023)
Abstract Background Nurses' secondary traumatic stress, compassion satisfaction and posttraumatic growth are closely related, but for newly graduated nurses, there are few reports to evaluate the specific path between these three. The aim of this study was to investigate examine the mediating role of compassion satisfaction in secondary traumatic stress and posttraumatic growth among newly graduated nurses. Methods From March 2021 to May 2021, a total of 330 newly graduated nurses from five tertiary hospitals in China were enrolled, and asked to complete questionnaires regarding secondary traumatic stress, compassion satisfaction and posttraumatic growth. Descriptive statistics, independent-samples T-test, one-way analysis of variance (ANOVA), Pearson correlation analysis and structural equation model were used in this study. A STROBE checklist was used to report findings. Results The scores of secondary traumatic stress, compassion satisfaction and posttraumatic growth of newly graduated nurses were 27.11 ± 4.94 (score range: 10-50), 31.89 ± 6.22 (score range: 10-50) and 56.47 ± 20.41 (score range: 0-100), respectively. Additionally, structural equation modeling showed that compassion satisfaction mediated the relationship between secondary traumatic stress and posttraumatic growth with the partial mediating effect of 0.089. Conclusions Newly graduated nurses may experience moderate secondary traumatic stress, but their posttraumatic growth is at a low level, and compassion satisfaction significantly affects the relationship between the two. Nursing managers should strengthen psychological evaluation, and promote their posttraumatic growth by improving their level of compassion satisfaction.